A 2-Step Strategy Combining FIB-4 With Transient Elastography and Ultrasound Predicted Liver Cancer After HCV Cure. (9th January 2022) - Ampuero, Javier; Carmona, Isabel; Sousa, Francisca; Rosales, Jose Miguel; López-Garrido, Ángeles; Casado, Marta; Figueruela, Banca; Aparicio, Ana; Andrade, Raúl; Guerra-Veloz, María Fernanda; Maraver, Marta; Pascasio, Juan Manuel; et al.
Abstract : INTRODUCTION: Despite the direct-acting antiviral therapy has dramatically decreased the likelihood of having liver-related complications and extrahepatic outcomes, the risk of developing hepatocellular carcinoma (HCC) is not totally eliminated after sustained virological response (SVR). We aimed to develop an easy-to-apply strategy to be adopted in clinical practice for accurately classifying the HCC risk in hepatitis C virus patients after SVR. METHODS: Prospective and multicenter study enrolling hepatitis C virus patients with advanced fibrosis (transient elastography [TE] > 10 kPa) or cirrhosis by ultrasound showing SVR. They were followed up until HCC, liver transplantation, death, or until October 2020, which occurred first, with a minimum follow-up period of 6 months after SVR (follow-up: 49 [interquartile range 28–59] months). RESULTS: Patients with cirrhosis by ultrasound represented 58% (611/1, 054) of the overall cohort. During the study, HCC occurrence was 5.3% (56/1, 054). Multivariate analyses revealed that Fibrosis-4 (FIB-4) > 3.25 (hazard ratio [HR] 2.26 [1.08–4.73]; P = 0.030), TE (HR 1.02 [1.00–1.04]; P = 0.045) and cirrhosis by ultrasound (HR 3.15 [1.36–7.27]; P = 0.007) predicted HCC occurrence. Baseline HCC screening criteria (TE > 10 kPa or cirrhosis) identified patients at higher risk of HCC occurrence in presence of FIB-4 > 3.25 (8.8%; 44/498) vs FIB-4 < 3.25 (2.4%; 12/506), while those with only FIB > 3.25 had no HCC (0%; 0/50) (logRank 22.129; P = 0.0001). A combination of baseline FIB-4 > 3.25 and HCC screening criteria had an annual incidence >1.5 cases per 100 person-years, while the rest of the groups remained <1 case. Patients who maintained post-treatment FIB-4 > 3.25 and HCC screening criteria remained at the highest risk of HCC occurrence (13.7% [21/153] vs 4.9% [9/184]; logRank 7.396, P = 0.007). DISCUSSION: We demonstrated that a two-step strategy combining FIB-4, TE, and ultrasound could help stratify HCC incidence risk after SVR.